2013
DOI: 10.1007/s10709-013-9718-5
|View full text |Cite
|
Sign up to set email alerts
|

Inferred kinship patterns reveal low levels of extra-pair paternity in the endangered Neotropical Jabiru Stork (Jabiru mycteria, Aves: Ciconiiformes)

Abstract: The present study inferred the genetic mating system in a natural breeding population of the Jabiru Stork (Jabiru mycteria), a Neotropical wading bird considered endangered in part of its distribution range. Based on data from eight microsatellite loci, maximum-likelihood kinship reconstruction techniques, parentage assignment analyses and effective population size (Ne) estimates were applied to samples collected in the Brazilian Pantanal wetland (N = 45 nestlings from 20 nests; N = 17 shed adult feathers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The trueN^normalb/trueN^normala ratios (Table ) were below the mean of 0.225 reported in a previous quantitative survey (Palstra & Fraser, ), except those calculated using Ntrue^b computed with the SA method for SG2 and the LD method overall. Nonetheless, trueN^normalb/trueN^normala ratios obtained in wood storks were often close to trueN^normale/trueN^normalc ratios reported for rare and endangered bird species (often <0.1) (e.g., Brekke, Bennett, Santure, & Ewen, ; Lopes, Miño, Rocha, Oliveira, & Del Lama, ; Ramstad, Colbourne, Robertson, Allendorf, & Daugherty, ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The trueN^normalb/trueN^normala ratios (Table ) were below the mean of 0.225 reported in a previous quantitative survey (Palstra & Fraser, ), except those calculated using Ntrue^b computed with the SA method for SG2 and the LD method overall. Nonetheless, trueN^normalb/trueN^normala ratios obtained in wood storks were often close to trueN^normale/trueN^normalc ratios reported for rare and endangered bird species (often <0.1) (e.g., Brekke, Bennett, Santure, & Ewen, ; Lopes, Miño, Rocha, Oliveira, & Del Lama, ; Ramstad, Colbourne, Robertson, Allendorf, & Daugherty, ).…”
Section: Discussionsupporting
confidence: 72%
“…Nonetheless, N b ∕N a ratios obtained in wood storks were often close to N e ∕N c ratios reported for rare and endangered bird species (often <0.1) (e.g., Brekke, Bennett, Santure, & Ewen, 2011;Lopes, Miño, Rocha, Oliveira, & Del Lama, 2013;Ramstad, Colbourne, Robertson, Allendorf, & Daugherty, 2013).…”
Section: Estimates Of N a And N B For Natural Populationssupporting
confidence: 72%
“…; 0.09 in jabiru stork Jabiru mycteria , Lopes et al . ). Given this wide range in avian N e / N c ranges, we cannot determine whether the low ratio in P. cabanisi reflects its cooperative mating system in the study area, other mechanisms related to its threat status, or a combination of both.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, rare and endangered species generally show much lower ratios, often below 0.1 (e.g. 0.03 in little spotted kiwi Apteryx owenii, Ramstad et al 2013; 0.09 in jabiru stork Jabiru mycteria, Lopes et al 2013). Given this wide range in avian N e /N c ranges, we cannot determine whether the low ratio in P. cabanisi reflects its cooperative mating system in the study area, other mechanisms related to its threat status, or a combination of both.…”
Section: N E To N C Ratiomentioning
confidence: 99%
“…Genetic methods allow us to overcome the potential shortcomings of purely observational studies when determining a given species’ mating system81314. Despite the wide-spread occurrence of social monogamy across avian species, recent research has found strict genetic monogamy to be the exception rather than the rule (e.g 2356789151617181920…”
mentioning
confidence: 99%